Cultural Moderation and Transformation in the Select Novels of Chetan Bhagat (International Journal of Food and Nutritional Sciences, 2022)
Economic Liberalization began in India in the early 1990s after the establishment of numerous multinational companies. Most of them were American IT based call centres, bank and business based outsourcing companies. India’s reputed educational institutions focussed on training graduates to cater to the needs of these companies, thereby making them employable in IT companies. Estimation states that 350000 employees work with IT companies in India, which makes one percent of India’s estimated workforce. Chetan Bhagat is regarded as an icon of Indian youth. He is unparalleled in representing the problems, anxiety and threats of Indian youth. The paper analyses the cultural deconstructions happened post economic liberalization in India, with special reference to the works of Chetan Bhagat